Prevalence and consumption patterns of energy drinks among Iraqi adolescents: A cross-sectional study - Soran Abdullah Al-keji; Samir Mahmood Othman (PLoS ONE, 2026)
Background Most energy drinks contain significant levels of caffeine, sugar, and other ingredients, which are consumed increasingly among adolescents. Excessive energy drinks consumption is associated with various adverse health effects. Objectives To investigate the prevalence and pattern of energy drink consumption among high school students in Erbil City, The Kurdistan Region, Iraq. Methods A cross-sectional study was conducted from October 15th, 2024 to March 15th, 2025. A multistage cluster sampling technique was used to recruit 800 students from 20 selected high schools in Erbil, Iraq. SPSS version 27 was used for data entry and analysis, a p-value ≤0.05 is considered statistically significant. Results Overall, 82.1% of participants had reported at least a one-time-consumption of energy drinks in their lives, and 57.6% had consumed them in the past 30 days. The prevalence of energy drink consumption was significantly higher among males (58.3%, p = 0.001). The study found a statistically significant association between gender (p = 0.001) and living arrangement (p = 0.023), and the prevalence of energy drink consumption. Conclusion The prevalence of energy drink consumption among high school-aged adolescents in Iraq was high, and associated with sociodemographic characteristics. The finding highlights the importance of considering gender differences in understanding energy drink consumption patterns. The study underscores the need for educational interventions to enhance students’ awareness of the health risks associated with energy drink consumption.